Risk Assessment of Occupational Accident of the Riggers at PT X Surabaya - Grace Stacyana Pasaribu (Universitas Airlangga, 2020)
Introduction: PT. X in Surabaya is a company specialized in the provision of freight services, both domestically and internationally. The loading and unloading services at PT. X is performed 24 hours a day; thus, the company regulates 3-shift divisions each day. The services are done by moving containers from a ship to chassis trucks or the other way around by using a crane operated by the STS operator and riggers. The loading and unloading services are believed as high-risk activities, since the workers are exposed to falling, slipping, being struck down by materials or containers, or being squeezed. Methods: This study applies the cross-sectional design with the observational approach. The variables of this study comprise hazard identification, risk assessment, risk control, and residual risk. The variable of risk assessment is done by applying the qualitative method. The primary data is obtained through observation and interview, while the secondary data is acquired from the company profile. Results: In the hazard identification, one low-risk hazard, 11 moderate-risk hazards, and ten high-risk hazards are discovered. Conclusion: It can be affirmed that as much as 45.45% of high-risk hazard is found amongst the riggers, such as the hands are squeezed by mooring ropes, being crushed by containers, falling from the heights, falling into a ship hatch, and being struck down or hit by twist locks.Keywords: loading and unloading, riggers, risk assessment